2005
DOI: 10.5551/jat.12.199
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Smoking: Relationship with Waist Circumference and Obesity-Related Disorders in Men Undergoing a Health Screening

Abstract: This study investigated whether smoking habits had a differential influence on waist circumference and obesity-related disorders in nonobese and obese men. We investigated 359 men with smoking habits confirmed by their spouses, including 172 nonobese men (BMI < 25) and 187 obese men (BMI ≥ ≥ ≥ ≥ ≥ 25). There were 113 nonobese smokers and 129 obese smokers. Obesity-related disorders were defined as hypertension, dyslipidemia, hyperglycemia, hyperuricemia, or treatment for one or more of these disorders. Nonobes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 13 publications
4
17
2
Order By: Relevance
“…There was also an association between alcohol intake, smoking and obesity which is consistent with existing research (Gornall, 2014;Mizuno et al, 2005). However, it must be noted that parents of children with DD drank less than parents of typically developing children.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…There was also an association between alcohol intake, smoking and obesity which is consistent with existing research (Gornall, 2014;Mizuno et al, 2005). However, it must be noted that parents of children with DD drank less than parents of typically developing children.…”
Section: Discussionsupporting
confidence: 88%
“…through health behaviours such as smoking etc). In fact, some have argued that engagement in unhealthy health behaviours such as smoking and alcohol use are associated with several long term mental health and physical health disorders including obesity (Bonevski, Regan, Paul, Baker, & Bisquera, 2014;Gornall, 2014;Mizuno et al, 2005;Suter, 2005). Although research on caregiver health behaviours is rather limited, one recent study has found that younger caregivers of patients with Alzheimer's disease smoke more than older carers (SalgadoGarcia et al, 2013), implying that younger caregivers may be more vulnerable and cope with the stresses of caring by smoking more.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were consistent with a previous study [31] . Mizuno et al [31] proposed that WC showed no difference between non-obese subjects with or without a smoking habit. Nonetheless, WC was significantly higher in obese subjects who smoked than those who did not.…”
Section: Discussionsupporting
confidence: 83%
“…In a study that used both obese and non-obese subjects divided into smoking and non-smoking groups, Mizuno et al reported that smokers had larger waist circumferences than never smokers among the obese subjects, suggesting that smoking may lead to increased abdominal fat accumulation [33]. However, the question that remains from this study is why, among the lipid profile factors, it affected only the HDL cholesterol.…”
Section: Discussioncontrasting
confidence: 50%